Dynamic nanomechanical properties of novel Si-rich intermetallic coatings growth on a medical 316 LVM steel by hot dipping in a hypereutectic Al-25Si alloy - Frutos, E; González-Carrasco, J L (Journal of the mechanical behavior of biomedical materials, 2015)
This aim of this study is to determine the elastoplastic properties of Ni-free Al3FeSi2 intermetallic coatings grown on medical stainless steel under different experimental conditions. Elastoplastic properties are defined by the plasticity index (PI), which correlates the hardness and the Young's modulus. Special emphasis is devoted to correlate the PI with the wear resistance under sliding contact, determined by scratch testing, and fracture toughness, determined by using a novel method based on successive impacts with small loads. With regard to the substrate, the developed coatings are harder and exhibit a lower Young's reduced modulus, irrespective of the experimental conditions. It has been shown that preheating of the samples prior to hot dipping and immersion influences the type and volume fraction of precipitates, which in turn also affect the nanomechanical properties. The higher the preheating temperature is, the greater the Young's reduced modulus is. For a given preheating condition, an increase of the immersion time yields a decrease in hardness. Although apparent friction coefficients of coated specimens are smaller than those obtained on AISI 316 LVM, they increase when using preheating or higher immersion times during processing, which correlates with the PI. The presence of precipitates produces an increase in fracture toughness, with values greater than those presented by samples processed on melted AlSi alloys with lower Si content (12 wt%). Therefore, these intermetallic coatings could be considered "hard but tough", suitable to enhance the wear resistance, especially when using short periods of immersion.
Keywords: modul pružnosti; vysoká teplota; Elastic Modulus; nanotechnologie; hliník; mechanické jevy; Mechanical Phenomena; Alloys; Stainless Steel; Silicon; Hot Temperature; slitiny; tvrdost; nerezavějící ocel; křemík; Nanotechnology; Biocompatible Materials; biokompatibilní materiály; Aluminum; Hardness